Long non‐coding RNA H19 suppresses retinoblastoma progression via counteracting miR‐17‐92 cluster. Issue 4 (2nd January 2018) - Zhang, Aihui; Shang, Weiwei; Nie, Qiaoli; Li, Ting; Li, Suhui
Abstract : Long non‐coding RNAs (lncRNAs) are frequently dysregulated and play important roles in many cancers. lncRNA H19 is one of the earliest discovered lncRNAs which has diverse roles in different cancers. However, the expression, roles, and action mechanisms of H19 in retinoblastoma are still largely unknown. In this study, we found that H19 is downregulated in retinoblastoma tissues and cell lines. Gain‐of‐function and loss‐of‐function assays showed that H19 inhibits retinoblastoma cell proliferation, induces retinoblastoma cell cycle arrest and cell apoptosis. Mechanistically, we identified seven miR‐17‐92 cluster binding sites on H19, and found that H19 directly bound to miR‐17‐92 cluster via these seven binding sites. Through binding to miR‐17‐92 cluster, H19 relieves the suppressing roles of miR‐17‐92 cluster on p21. Furthermore, H19 represses STAT3 activation induced by miR‐17‐92 cluster. Hence, our results revealed that H19 upregulates p21 expression, inhibits STAT3 phosphorylation, and downregulates the expression of STAT3 target genes BCL2, BCL2L1, and BIRC5. In addition, functional assays demonstrated that the mutation of miR‐17‐92 cluster binding sites on H19 abolished the proliferation inhibiting, cell cycle arrest and cell apoptosis inducing roles of H19 in retinoblastoma. In conclusion, our data suggested that H19 inhibits retinoblastoma progression via counteracting the roles of miR‐17‐92 cluster, and implied that enhancing the action of H19 may be a promising therapeutic strategy for retinoblastoma. Abstract : Long non‐coding RNA (lncRNA) H19 is downregulated in retinoblastoma, and inhibits retinoblastoma cell proliferation, induces retinoblastoma cell cycle arrest, and cell apoptosis.H19 directly bound to miR‐17‐92 cluster via seven binding sites of miR‐17‐92 cluster on H19.H19 relieves the suppressing roles of miR‐17‐92 cluster on p21 and represses STAT3 activation induced by miR‐17‐92 cluster.